Resistance of the mucous membrane of the oral cavity during hypertrophy of the lingual tonsil - Аndreev A. V.; Таgunova I. K.; Nasibullin, B. A.; Gushcha, S. G.; Volyanska, V. S.; Movlyanova, N. V.; Badiuk, N. S. (Journal of Education, Health and Sport, 2020)
The article presents the results of studies that indicate that with hypertrophy of the lingual tonsil, weakening of the resistance of the oral mucosa to external influences is observed. This is due to sensitization, intoxication, depletion of the body by various pathogens that disrupt the regulation and repair processes in the body.